Exploring Historical Seismic Events Through Secondary Data Analysis: Implications for Understanding Submarine Earthquakes in Marine Geophysics for Educational Purposes - K. Haritha (Universitas Pendidikan Indonesia (UPI), 2023)
Understanding historical seismic events is crucial for studying submarine earthquakes and their implications in marine geophysics for educational purposes. This research paper aims to explore the potential of secondary data analysis in unraveling the characteristics and behavior of submarine earthquakes. By utilizing historical seismicity data, including seismic recordings, catalogs, and reports, this study investigates the spatiotemporal patterns, magnitude-frequency relationships, and recurrence intervals of submarine earthquakes. The paper discusses the methodologies employed for data compilation, processing, and analysis, highlighting the challenges and limitations associated with utilizing secondary data. Furthermore, it presents case studies showcasing the application of secondary data analysis in identifying earthquake-prone regions, characterizing fault systems, and assessing seismic hazards in marine environments. The findings emphasize the significance of historical seismic data in improving our understanding of submarine earthquakes and informing geophysical studies related to seismic hazard assessment, tectonic processes, and plate boundary interactions in the marine realm. The paper concludes with recommendations for future research and the potential integration of secondary data analysis with real-time monitoring systems to enhance seismic event detection and characterization in marine geophysics.